What means civic education in a digitalized world? - Schmitt, Josephine B.; Baake, Jasmin; Kero, Sandra (Frontiers in Psychology, 2024)
The hope of reaching diverse and large target groups has motivated civic education practitioners to offer their content on social media. The question has therefore long ceased to be whether civic education should take place on the internet, but rather how civic education goals can be implemented digitally to foster civic literacy. At first glance, the possibility of reaching a broad audience in a short time seems tempting. At a second glance, social media reveals several challenges that can impair educational processes. The present paper discusses the following questions: What are the opportunities and pitfalls of civic education in social media? How can we ensure successful civic education in a digitalized world? In our article, we want to provide an interdisciplinary perspective on the topic by drawing among others from the literature in the fields of media psychology, communication studies, and education science. By integrating insights from various disciplines, our paper seeks to enrich the academic dialogue and to promote a nuanced understanding of the evolving dynamics of civic education in the digital realm. With its practical focus, our paper further aims to underscore the applicability of scientific research.